Stakeholder Analysis Using The Vectorized Salience Model, Enhanced Power-Interest Grid, And Stakeholder Cube Diagrams - Sarungu, Cornelius Mellino (ULTIMA InfoSys, 2024)
Abstract—Stakeholders are parties affected by a project, with both positive and negative impacts. In a project, the expectations of these stakeholders must be managed properly, and a project manager plays an important role in satisfying and balancing the interests that exist between them. The stakeholder analysis process needs to be carried out in detail. It must also be supported by the right tools so that it can reveal new insights that may have been hidden behind the stakeholder data. In this research, two techniques are proposed to increase the acuity of two tools that are often used in the stakeholder analysis process, namely the salience diagram and the power grid diagram. Improvements were made by using vectorization techniques for salience diagrams and applying Gartner's magic quadrant method to power grid diagrams. Both improvements can show more clearly the position of stakeholders in the categorization formed according to the two tools. Of course, this will further assist the project team in determining the right strategy for each stakeholder so that all elements support the project’s success.